2003
DOI: 10.1023/a:1026156222685
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the present investigation, length-weight relationship, condition factor, age, growth, mortality, gonadosomatic index (GSI) and fecundity of tilapias (Bolti in Arabic): Oreochromis niloticus, from Shanawan drainage canal (SDC), Al-Minufiya Province, Egypt, were studied. This was carried out on 162 fish samples collected during the period from April 1992 to May 1993. Oreochromis niloticus was found to attain sexual maturity early (8-9 cm), was more fecund (1,234-3,893) and has high mortality rates (91% for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Many factors can shape the CF, such as sex, season, nutrition status, or water quality and temperature (Garcia-Abiado et al, 2004;Swansburg et al, 2002;Khallaf et al, 2003;Nehemia et al, 2012). Independently of the particular influences, Data given as mean (coefficient of variation).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can shape the CF, such as sex, season, nutrition status, or water quality and temperature (Garcia-Abiado et al, 2004;Swansburg et al, 2002;Khallaf et al, 2003;Nehemia et al, 2012). Independently of the particular influences, Data given as mean (coefficient of variation).…”
Section: Discussionmentioning
confidence: 99%
“…Safe drinking water is one of the basic requirements for human health, development and wellbeing (1). Access to safe drinking water and hygienic living conditions is a global concern and these issues are especially serious in developing countries (2).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these variations might be influenced by the reproductive status and general physiological condition of the fish and thereby affecting their sensitivity to E-EDCs [ 65 ]. Many studies have reported that fish growth can be reduced in polluted water [ 66 , 67 ]. The inhibition of gonadal growth could be attributed to xenosteroids found in the effluents discharged from the Bahr El-Baqar drain into the investigated sites.…”
Section: Discussionmentioning
confidence: 99%